STUDI PERILAKU KUAT GESER BALOK BETON BERTULANG MEMADAT SENDIRI DENGAN SERAT âPOLYPROPYLENEâ - Lisantono, A.; Praja, B.A.; Prasetio, H.K. (CANTILEVER, 2018)
This paper presents a study of the behavior of self compacting reinforced concrete with polypropylene fiber. Four self compacting reinforecd concrete beam specimens were cast and tested in this study. Two beams were cast without fiber and two beams were cast with polypropylene fiber. The proportion of polypropylene fiber was 0.9 kg/m of the weight of concrete and the proportion of silica fume was 10 % of the weight of portland cement. The dimension of the beam was (180Ã260) mm with 2000 mm length. Two longitudinal bars with Ã10 mm were placed at the top of the beam as compressive bars and three longitudinal bars with Ã10 mm were placed at the bottom of the beam as tensile bars. Shear reinforcement with Ã8 mm with spacing of 150 mm were placed at the midle, and there were no stirrups at the shear region. Several cylinder specimens with size of (150Ã300) mm and beam without reinforcement with size of (200Ã200Ã700) mm were also cast and tested to determine the mechanics properties of concrete such as compressive strength, tensile strength, modulus of elasticity and modulus of ruptures. The result show that the compressive strength and modulus of elasticity of self compacting concrete with polypropylene fiber were decreased 26.98 % and 9.98 %, respectively compare to the self compacting concrete without fiber. While the tensile strength and modulus of ruptures of the self compacting concrete with polypropylene fiber were increased 2.76 % and 3.65 %, respectively compare to the self compacting concrete without fiber. The shear capacities of the self compacting concrete beams without fiber were 62.76 kN and 63.44 kN. While the shear capacities of the self compacting concrete beams with polypropylene fiber were 60.77 kN and 50.61 kN.